(-)-Carveol Prevents Gastric Ulcers via Cytoprotective, Antioxidant, Antisecretory and Immunoregulatory Mechanisms in Animal Models - Serafim, Catarina Alves de Lima; Araruna, Maria Elaine Cristina; Alves Júnior, Edvaldo Balbino; Silva, Leiliane Macena Oliveira; Silva, Alessa Oliveira; da Silva, Marcelo Sobral; Alves, Adriano Francisco; Araújo, Aurigena Antunes; Batista, Leônia Maria (Frontiers in Pharmacology, 2021)
Background: (-)-Carveol (p-Mentha-6,8-dien-2-ol) is a monocyclic monoterpene alcohol present in essential oils of plant species such as Cymbopogon giganteus, Illicium pachyphyllum, and in spices such as Carum carvi (cumin). Pharmacological studies report its antitumor, antimicrobial, neuroprotective, vasorelaxant, antioxidant, and anti-inflammatory activity. Hypothesis/Purpose: This study evaluates the acute non-clinical oral toxicity, the gastroprotective activity of monoterpene (-)-Carveol in animal models, and the related mechanisms of action. Methods: Acute toxicity was assessed according to OECD guide 423 in mice. Ethanol, stress, NSAIDs, and pylorus ligation-induced gastric ulcer models were used to investigate antiulcer properties. The related mechanisms of action were investigated using the ethanol-gastric lesions protocol. Results: (-)-Carveol has low toxicity, with a lethal dose of 50% (LD50) equal to or greater than 2500 mg/kg, according to OECD guide nº 423. In all gastric ulcer induction methods evaluated, (-)-Carveol (25, 50, 100, and 200 mg/kg, p.o.) significantly reduced the ulcerative lesion in comparison with the control groups. To investigate the mechanisms involved in the gastroprotective activity, the antisecretory or neutralizing of gastric secretion, cytoprotective, antioxidant, and immunoregulatory effects were evaluated. In the experimental protocol of pylorus ligation-induced gastric ulcer, (-)-Carveol (100 mg/kg) reduced (p<0.001) the volume of gastric secretion in both routes (oral and intraduodenal). The previous administration of blockers NEM (sulfhydryl groups blocker), L-NAME (nitric oxide synthesis inhibitor), glibenclamide (KATP channel blocker), and indomethacin (cyclo-oxygenase inhibitor), significantly reduced the gastroprotection exercised by (-)-Carveol, suggesting the participation of these pathways in its gastroprotective activity. In addition, treatment with (-)-Carveol (100 mg/kg) increased mucus adhered to the gastric wall (p<0.001). Treatment also increased levels of reduced glutathione (GSH), superoxide dismutase (SOD), and interleukin-10 (IL-10) (p<0.001). It also reduced malondialdehyde (MDA), myeloperoxidase (MPO), interleukin-1 beta (IL-1β), and tumor necrosis factor-alpha (TNF-α) levels (p<0.001). Conclusion: Thus, it is possible to infer that (-)-Carveol presents gastroprotective activity related to antisecretory, cytoprotective, antioxidant, and immunomodulatory mechanisms.